Conception et production d’un manuscrit enluminé atypique - Irène Fabry-Tehranchi (Perspectives Médiévales, 2017)
Design and production of an atypical illuminated manuscript : the collaborative and progressive conception of New Haven, Yale, Beinecke, MS 227 (1357).New Haven, Yale University, Beinecke Library, MS 227, produced in the mid-fourteenth century in Northern of France, contains the Joseph, the Estoire del saint Graal, the Merlin and its Vulgate Sequel. This codicological, paratextual and visual examination centred on the Merlin and its sequel underlines the complexity and singularity of this manuscript’s conception.Yale, MS 227 contains several types of illustrations: miniatures placed either in the text or in the lower margin of the folio, and small initials. The marginalia of this manuscript are exceptional: they are not grotesque drolleries, but are modelled, both by their format and their iconographic content, on the miniatures inserted in the text, which they seem to complete. The marginal annotations of Yale, MS 227 highlight the different stages of its production, linking text, paratext and illustrations. These elements, which refer to three distinct geographical areas, demonstrate the complexity of codex, the product of a collective and collaborative undertaking.